INOVASI PERENCANAAN PENDIDIKAN BERBASIS EKOSISTEM DIGITAL - Hidayah, Lailatul; Muchammad Eka Mahmud; Akhmad Muaddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of digital technology necessitates a restructuring of the governance system of educational organizations during the planning stage. This study aims to analyze the urgency of transforming conventional management systems toward digital ecosystem-based educational planning innovation, map the key components that form an interoperable ecosystem, and formulate strategic solutions for its implementation. The research method used is a qualitative approach with a systematic literature review. Data were collected through digital searches in scientific indexing databases with strict inclusion criteria on 10 reputable journal articles (published 2024–2026) that were relevant, then analyzed using content analysis techniques and thematic synthesis of qualitative findings. The results show that current educational planning innovation has shifted toward the Agile Digital Planning Model, which integrates ICT infrastructure pillars, digital curriculum readiness, and macro data-based monitoring standardization. The success of this innovation heavily depends on the adaptive capacity of human resources (HR) managing the system. Systemic barriers such as sectoral data ego, infrastructure disparities, and cultural resistance to change can be substantially reduced through single-platform policies, cloud computing optimization, and the reconstruction of a data-driven organizational culture. The significance of this research provides a theoretical contribution in the form of a visionary conceptual model that can serve as a strategic reference for policymakers in designing a blueprint for adaptive, accountable, and futuristic educational planning to address global uncertainty in the digital era.